Gastric Neuroendocrine Tumour and Pernicious Anemia in a Young Male: Case Report - Leite, Ana Bento; Veiga, Luis; Mesquita, Gonçalo; Novo, Filipa; Campos, Anita (Brazilian Journal of Case Reports, 2025)
Gastric neuroendocrine tumours (G-NETs) are rare, but incidence is increasing due to the broader use of endoscopy. Most of them are asymptomatic and incidentally detected on endoscopy. Their prognosis is associated with histological grade. Type 1 G-NETs are the most common subtype and are typically associated with chronic atrophic gastritis (CAG) and pernicious anaemia (PA), conditions that impact cyanocobalamin (vitamin B12) absorption. The authors report a case of a 44-year-old male with paresthesias of upper and lower limbs, cyanocobalamin deficiency, positive parietal cell antibodies and severe sensory motor polyneuropathy. Upper endoscopy revealed CAG and gastric polyp. Histopathology confirmed a well-differentiated type 1 G-NET. He was treated with cyanocobalamin supplementation and mucosectomy. Surveillance endoscopy was recommended. This case highlights the diagnostic complexity of type 1 G-NETs in young patients with PA, demonstrating the connection between these conditions and underscores the importance of multidisciplinary management strategies.